2021
DOI: 10.1155/2021/5491017
|View full text |Cite
|
Sign up to set email alerts
|

Research on Key Algorithms of the Lung CAD System Based on Cascade Feature and Hybrid Swarm Intelligence Optimization for MKL‐SVM

Abstract: Feature selection and lung nodule recognition are the core modules of the lung computer-aided detection (Lung CAD) system. To improve the performance of the Lung CAD system, algorithmic research is carried out for the above two parts, respectively. First, in view of the poor interpretability of deep features and the incomplete expression of clinically defined handcrafted features, a feature cascade method is proposed to obtain richer feature information of nodules as the final input of the classifier. Second, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Chang et al proposed a pulmonary nodule identification algorithm based on machine learning, finally carried out the algorithm construction experiment on the cooperative hospital dataset, and compared it with 8 advanced algorithms on the public dataset LUNA16. e final experimental results show that the proposed algorithm can improve the accuracy of pulmonary nodule recognition and can reduce the missed detection of nodules [3]. Sarkar et al used an optimized machine learning algorithm to predict the outcome of accidents such as injuries, near misses, and property damage using occupational accident data and finally validated the effectiveness of the proposed method through experiments [4].…”
Section: Related Workmentioning
confidence: 95%
“…Chang et al proposed a pulmonary nodule identification algorithm based on machine learning, finally carried out the algorithm construction experiment on the cooperative hospital dataset, and compared it with 8 advanced algorithms on the public dataset LUNA16. e final experimental results show that the proposed algorithm can improve the accuracy of pulmonary nodule recognition and can reduce the missed detection of nodules [3]. Sarkar et al used an optimized machine learning algorithm to predict the outcome of accidents such as injuries, near misses, and property damage using occupational accident data and finally validated the effectiveness of the proposed method through experiments [4].…”
Section: Related Workmentioning
confidence: 95%
“…Our results indicated that compared with the tandem strategy in other radiomic models, the MKL-SVM algorithm with a linear convex combination of polynomial kernel and sigmoid kernel could effectively fuse bimodal data with better performance in differential diagnosis. The MKL has been demonstrated to improve classification accuracy and robustness [35] . It is impossible to construct a universal optimal learning algorithm in all fields.…”
Section: Discussionmentioning
confidence: 99%
“…After image preprocessing consistent with the literature 55 , 1140 ROI images of candidate nodules with a size of 64*64 were selected as the experimental dataset. Specifically, 650 images of solitary lung nodules and 490 non-nodule images were included.…”
Section: Experimental Datasetmentioning
confidence: 99%